PENINGKATAN KEPERCAYAAN DIRI ANAK USIA 3-4 TAHUN MELALUI METODE ROLE PLAYING DI PAUD MELATI PUJER BONDOWOSO - Imamah, Noer; Firman Ashadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Self-confidence is one of the essential aspects of early childhood socio-emotional development because it influences children's ability to interact, communicate, and participate in learning activities. Preliminary observations conducted at PAUD Melati Pujer Bondowoso revealed that most children aged 3–4 years lacked the confidence to perform in front of the class, answer teachers' questions, present their work, and interact with teachers and peers. This study aims to improve the self-confidence of children aged 3–4 years through the implementation of the role-playing method. The research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, consisting of planning, action, observation, and reflection stages conducted in two cycles. The participants were ten children in Group A at PAUD Melati Pujer Bondowoso. Data were collected through observation using a self-confidence observation sheet and analyzed descriptively using percentage techniques supported by qualitative descriptions. The study is expected to demonstrate that the implementation of the role-playing method can improve children's self-confidence across all observed indicators. The findings are expected to provide an effective learning strategy for enhancing socio-emotional development, particularly self-confidence, in early childhood education.